Diet Quality Index for older adults (DQI-65): development and use in predicting adherence to dietary recommendations and health markers in the UK National Diet and Nutrition Survey. Issue 11 (14th December 2022) - Dorrington, Nicole; Fallaize, Rosalind; Hobbs, Ditte; Weech, Michelle; Lovegrove, Julie Anne
Abstract: Diet quality indexes (DQI) are useful tools for assessing diet quality in relation to health and guiding delivery of personalised nutritional advice; however, existing DQI are limited in their applicability to older adults (aged ≥ 65 years). Therefore, this research aimed to develop a novel evidence-based DQI specific to older adults (DQI-65). Three DQI-65 variations were developed to assess the impacts of different component quantitation methods and inclusion of physical activity. These were Nutrient and Food-based DQI-65 (NFDQI-65), NFDQI-65 with Physical Activity (NFDQI-65+PA) and Food-based DQI-65 with Physical Activity (FDQI-65+PA). To assess their individual efficacy, the NFDQI-65, NFDQI-65+PA and FDQI-65+PA were explored alongside the validated Healthy Eating Index-2015 (HEI-2015) and Alternative Healthy Eating Index-2010 (AHEI-2010) using data from the cross-sectional UK National Diet and Nutrition Survey (NDNS) rolling programme. Scores for DQI-65 variations, the HEI-2015 and AHEI-2010 were calculated for adults ≥ 65 years from years 2–6 of the NDNS ( n 871). Associations with nutrient intake, nutrient status and health markers were analysed using linear and logistic regression. Higher DQI-65 and HEI-2015 scores were associated with increased odds of meeting almost all our previously proposed age-specific nutritional recommendations, and with important health markers of importance for older adults, including lower BMI, lower medication use and lower C-reactive protein ( P < 0·01). Few associations were observed for the AHEI-2010. This analysis suggests value of all three DQI-65 as measures of dietary quality in UK older adults. However, methodological limitations mean further investigations are required to assess validity and reliability of the DQI-65.